Promosi Online Untuk Meningkatkan Penjualan Kerupuk Sebring Rasa Rindu Pada Desa Padang Hangat - Putra, Iswidana Utama; Harwini, Dewi; Sakina, Nabilla Dwi (Jurnal Gotong Royong, 2025)
This community service program aimed to increase the sales of Kerupuk Sebring “Rasa Rindu,” a traditional cracker product from Padang Hangat Village, through online promotion using Instagram. The product is part of a home-based business that faces challenges in utilizing social media effectively for marketing. The Asset-Based Community Development (ABCD) approach was applied to identify and optimize local assets such as the unique product, local skills, and existing digital tools. Activities included digital marketing training, Instagram optimization, and visual content creation. The program led to a rise in Instagram followers from 0 to 107 and initiated interaction with potential buyers. These results indicate that consistent digital promotion can expand market reach and enhance brand awareness. It is hoped that this home business will continue to grow and contribute to the local economy.